PENENTUAN STRATEGI PEMASARAN KARTU GSM MENGGUNAKAN TEORI PERMAINAN FUZZY - Nurcahyo Nurcahyo; Tabah Heri Setiawan (LPPM Universitas Bina Bangsa, 2022)
Lately, many people tend to use GSM cards to meet their needs. Good for sending short messages, calling, using social media, and so on. According to research, the latest research notes that internet use in Indonesia from students is predicted to reach 30 million. This study traces the online activity of a sample of students involving 400 respondents aged 10-19 years in Bogor district and representing urban and rural areas. As many as 98% claimed to be internet users. Source: kompas.com. The number of GSM card makers, such as Indosat, XL-Axiata, Telkomsel, and others, creates a lot of confusion among students in using the GSM starter pack because it doesn't suit their needs, so they often change the GSM starter card. Therefore, the purpose of the research is so that students can choose the GSM card wisely according to their needs in the form of analysis data and so that the analysis data can be used by GSM companies in marketing the starterpack. This study uses the game theory method with data sources from direct sources who interviewed 100 students in the Bogor district asrespondents. Based on the analysis carried out, it is concluded that the signal strength that gets the greatest results is 8.193. This proves that people, especially students, use GSM cards, judging from the strong signal of a GSM card.